2013
DOI: 10.1542/peds.2013-0040
|View full text |Cite
|
Sign up to set email alerts
|

Visual Processing in Adolescents Born Extremely Low Birth Weight and/or Extremely Preterm

Abstract: BACKGROUND AND OBJECTIVES Ocular growth and development differs between preterm and term-born infants and may cause long-term negative consequences for visual function, but contemporary data on long-term visual outcomes in representative samples of the highest risk extremely low birth weight (ELBW, <1000 g birth weight) or extremely preterm (EP, <28 weeks’ gestation) survivors are lacking. Our objective was to compare visual functioning between ELBW/EP and normal birth weight (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 50 publications
4
27
0
1
Order By: Relevance
“…Similarly, an Australian study in late adolescents aged 14–20 years reported that participants with formerly extreme low BW and extreme preterm infants compared with normal BW infants had significantly worse visual acuities, poorer stereopsis and poorer convergence 16. There are limited data based on assessing the association of visual acuity and BW in adults with a particular lack of population-based data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, an Australian study in late adolescents aged 14–20 years reported that participants with formerly extreme low BW and extreme preterm infants compared with normal BW infants had significantly worse visual acuities, poorer stereopsis and poorer convergence 16. There are limited data based on assessing the association of visual acuity and BW in adults with a particular lack of population-based data.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies on late adolescents (age 14–20 years)16 and in a Danish study of 4300 conscripts,17 an association was observed between low BW and reduced visual acuity, whereas there is no population-based data for the impact far beyond childhood. Furthermore, varying data exist for the association with refractive error.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a prospective, population-based study of extremely low birthweight (ELBW) children from Victoria, Australia, born in the era of ROP treatment, reported more problems in visual perception at age 14–20 years (OR 3.09) compared with controls 31. A subsequent MRI study in the same ELBW cohort reported alterations in both the optical radiation and visual cortex compared with controls, which may be related to the visual findings 32.…”
Section: Discussionmentioning
confidence: 99%
“…Certain studies recommend that low birth weight or extreme preterm birth can play a role. 3 It is also believed that minor traumatic brain injury could lead to visual processing issues, but then again there is no adequate evidences to completely support that concept. 4 It is also very difficult to identify visual processing issues in children.…”
Section: Visual-motor Handling Issuesmentioning
confidence: 99%